2008
DOI: 10.1213/ane.0b013e318172fa74
|View full text |Cite|
|
Sign up to set email alerts
|

Palonosetron Exhibits Unique Molecular Interactions with the 5-HT3 Receptor

Abstract: Palonosetron exhibited allosteric binding and positive cooperativity when binding to the 5-HT(3) receptor. Palonosetron also triggered functional effects that persisted beyond its binding to the 5-HT(3) receptor at the cell surface. Differences in binding and effects on receptor function may be relevant to the unique beneficial actions of palonosetron. To our knowledge, this is the first report showing palonosetron's interaction with the 5-HT(3) receptor at the molecular level, clearly differentiating it from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
163
0
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 214 publications
(176 citation statements)
references
References 21 publications
3
163
0
4
Order By: Relevance
“…[13][14][15][16][17] Palonosetron may also have other advantages for perioperative care. For example, a recent study reported by Cho et al 34 found that palonosetron 0.075 mg iv administered before induction of anesthesia reduced injection pain associated with rocuronium administration; the NNT was 2.94.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[13][14][15][16][17] Palonosetron may also have other advantages for perioperative care. For example, a recent study reported by Cho et al 34 found that palonosetron 0.075 mg iv administered before induction of anesthesia reduced injection pain associated with rocuronium administration; the NNT was 2.94.…”
Section: Discussionmentioning
confidence: 99%
“…Méthodes Nous avons effectué une recherche systématique dans les bases de données MEDLINE Ò , EMBASE TM , le Registre central Cochrane des essais cliniques contrô lés et Web of Science Ò pour identifier les essais randomisés contrô lés qui ont abordé la comparaison de l'efficacité antiémétique dans les 24 premières heures suivant une chirurgie, du palonosétron et de l'ondansétron administrés à titre prophylactique. Les principaux critères d'évaluation étaient le pourcentage de participants éprouvant des nausées postopératoires (NPO), des vomissements postopératoires (VPO) ou les deux, dans la période précoce (0-6 heures) ou tardive (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) Postoperative nausea and vomiting (PONV), the big ''little problem'', 1 is the most common postoperative medical problem. From the perspective of both patients and healthcare providers, prophylaxis of PONV is equally as important as postoperative analgesia.…”
Section: Résuméunclassified
See 1 more Smart Citation
“…Our data indicate that palonosetron shows long-lasting activity that may be related to its longer half-life and its unique interaction with the 5-HT 3 receptor. 35 In fact, palonosetron seems to show positive cooperativity with the 5-HT 3 receptor, and thus the binding affinity increases, as additional palonosetron molecules become bound to the receptor. This characteristic, which is not shared by firstgeneration 5-HT 3 RAs, may partly account for the effective clinical control of CINV observed with palonosetron.…”
Section: Discussionmentioning
confidence: 99%
“…Palonosetron (Pal), a novel 5-HT3 antagonist, is an effective antiemetic in the setting of PONV that also has advantages in treating PDNV due to its prolonged duration *Address correspondence to this author at the Department of Anesthesiology, NYU Langone Medical Center, 550 1 st Ave RR 605, New York, NY 10016; Tel: 212-263-0667; Fax: 212-263-3211; E-mail: Sorosch.Didehvar@nyumc.org of action. Palonosetron exhibits greater binding affinity and has a longer half-life than older 5-HT3 antagonists, possibly due to its binding of 5HT-3 receptors in an allosteric, positively cooperative manner [5][6][7]. Prior studies have demonstrated the advantages of a multimodal approach to the treatment of PONV, including a reduction in the incidence of PONV in high risk patients with the combination of 5-HT3 receptor antagonists and dexamethasone [8,9].…”
Section: Introductionmentioning
confidence: 99%